1972
DOI: 10.1139/z72-061
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Ixodes cookei Packard (Ixodidae) of groundhogs (Marmota monax Erxleben)

Abstract: KO, R. C. 1972. Biology of Ixodes cookei Packard (Ixodidae) of groundhogs (Marmota monax Erxleben).Can. J. Zool. 50: 433436. Observations were made on the biology of the tick under natural conditions in southern Ontario and in the laboratory at 30C and 90-95% relative humidity. Twenty-nine percent of 569 groundhogs examined from March to September during 1969 and 1970 were infested with I. cookei. Four hundred and forty-four I. cookei were collected; most females were recovered in May and larvae in August. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…CDC https://www.cdc.gov/ticks/tickbornediseases/tickID.html). Yet, previous literature on I. cookei clearly describes it as a cosmopolitan species that parasitizes a wide range of medium-sized mammals [53,67]. Our data support the observations that this species can be found parasitizing human, domestic animals, and wild animals.…”
Section: Discussionsupporting
confidence: 88%
“…CDC https://www.cdc.gov/ticks/tickbornediseases/tickID.html). Yet, previous literature on I. cookei clearly describes it as a cosmopolitan species that parasitizes a wide range of medium-sized mammals [53,67]. Our data support the observations that this species can be found parasitizing human, domestic animals, and wild animals.…”
Section: Discussionsupporting
confidence: 88%
“…The I. cookei tick, which frequently parasitizes groundhogs and mustelids, is believed to be nidicolous and does not exhibit questing behavior (Ko 1972). Generations of I. cookei are closely associated with a single host in its burrow, so humans are less likely to come into contact with POWV-infected I. cookei (Hinten et al 2008, Ebel 2010).…”
Section: Powassan Virus Transmissionmentioning
confidence: 99%
“…In Minnesota, Green et al (1943) reported average infestations of more than 3000 ticks on snowshoe hare (Lepus americanus) in late summer, with as many as 16 000 ticks found on one animal. There are numerous published records for H. leporispalustris in Canada (Hewitt 1915;Hearle 1938;Bequaert 1945;Brown and Kohls 1950;Judd 1953;Scholten et al 1962;Wilson 1967;Martell et al 1969;Ko 1972a;Wright 1979;Jones and Thomas 1980;Gkoroba 1980) with few specifics on the life cycle and natural history. The most detailed studies on its natural history were carried out in Nova Scotia by Campbell and Glines (1979) in the laboratory and by Green et al (1943) and Campbell et al (1980) in the field in Minnesota and Nova Scotia, respectively.…”
Section: Haemaphysalis Leporispalustris (Packard)mentioning
confidence: 99%
“…In Canada, Ixodes cookei is primarily associated with the woodchuck, Marmota monax, where prevalence has been reported from 29-50% (McLean et al 1966;Ko 1972a;Artsob et al 1984;Farkas and Surgeoner 1990), though Martell et al (1969) found three of seven porcupines infested in Nova Scotia. In southern parts of its range, mediumsized mammals, especially raccoons and skunks, are important hosts (e.g., Sonenshine 1979b; Kollars and Oliver 2003).…”
Section: Ixodesmentioning
confidence: 99%
See 1 more Smart Citation